The teaching method of “siplaecec” in language learning: The conditional role subject to need climate within a self-determination theory framework - Zhang, Qi (American Journal of Social Sciences and Humanities, 2025)
This study investigates, framed within Self-Determination Theory (SDT), how need climate (Need-supportive versus need-thwarting) and teaching method (“Siplaecec” featuring scaffolded interactive play, ludic autonomous engagement, and competence-embedded context versus “traditional method” through didactic instruction) interact to influence language learning outcomes. A two-way ANCOVA measures the interaction effect, controlling for pre-intervention performance, to examine the potential synergistic relationship between the need climate and teaching method. The results demonstrate that the need climate alone has a significant main effect on learning outcomes, with need-supportive environments outperforming need-thwarting conditions. In contrast, the teaching method alone reveals a non-significant main effect, indicating that innovative pedagogy does not necessarily facilitate learning in isolation. Notably, the results highlight a disordinal interaction effect. Explicitly speaking, learners in the group of “siplaecec” employed in need-supportive climates have achieved the highest outcomes, while those in the group of “siplaecec” employed in need-thwarting climates have achieved the lowest outcomes. Traditional methods have yielded relatively stable effects regardless of need climates. These findings suggest the conditional efficiency of pedagogical innovation, the potential persistence-stimulating role of need frustration, and the resilience of traditional methods in buffering against the debilitating influences of unsupportive environments. This study extends the principles of SDT and presents the climate-sensitive implementation of play-related pedagogies.